Extraction and identification of certain bioactive compounds with antibacterial activity from the green algae Cladophora glomerate - Mohammed, Ali Hussein; Lhwak, Nasser Salh; Jabbar, Ahmed Abdulhadi (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Cladophora glomerata algae extract was used to inhibit the growth of five bacterial species: Escherichia coli, Staphylococcus aureus, Proteus mirabilis, Citrobacter, and Klebsiella pneumoniae. Algae samples were collected from the river Euphrates in Al-Fadhiliya/Thi-Qar governorate and extracted into alcohol. The concentrations of the extracts were compared with five antibiotics. The 200% concentration showed the highest effectiveness against bacteria, with an inhibition zone of 28mm. The antibiotics Imipenem and Meropenem had an inhibition zone of 28mm, while Amikacin, Norfloxacin, and Piperacillin had an inhibition area of 12-21mm. The 20% concentration was least effective against E. coli, with an inhibition diameter of 2mm. The alcoholic extract of C. glomerata alga had the highest inhibition region of 28 against K. pneumonia and 13mm against P. mirabilis. The chemical algal contents were identified using mass GC technology, revealing compounds like 10-Undecyn-1-ol, n-hexadecanoic acid, 4,4-dimethyl-1-hex, and isoamyl nitrite, which were found to have the major function of inhibiting bacterial growth